High Performance H2−Mn Regenerative Fuel Cells through an Improved Positive Electrode Morphology - Javier Rubio-Garcia; Anthony Kucernak; Barun Kumar Chakrabarti; Dong Zhao; Danlei Li; Yuchen Tang; Mengzheng Ouyang; Chee Tong John Low; Nigel Brandon (Batteries, 2023)
The effective scaling-up of redox flow batteries (RFBs) can be facilitated upon lowering the capital costs. The application of ubiquitous manganese along with hydrogen (known as H2−Mn regenerative fuel cells (RFC)) is seen as an effective solution for this purpose. Here, we aim to evaluate different positive electrodes so as to improve the key performance metrics of the H2/Mn RFC, namely electrolyte utilization, energy efficiency, and peak power densities. Commercially available carbon paper and graphite felt are used to show that the latter provides better key performance indicators (KPIs), which is consistent with the results reported for standard all-vanadium RFBs in the literature. Even better KPIs are obtained when an in-house carbon catalyst layer (CCL) is employed in combination with graphite felt electrodes (e.g., more than 80% energy efficiency, >0.5 W cm−2 peak power density and electrolyte utilization of 20 Ah L−1 for felt and carbon metal fabric (CMF), prepared by means of electrospinning and carbonization, in comparison with about 75% energy efficiency 0.45 W cm−2 peak power density and 11 Ah L−1 electrolyte utilization for felt on its own). It is envisaged that if the electrochemical performance of CCLs can be optimized then it could open up new opportunities for the commercial exploitation of H2−Mn systems.